An attributional approach to explaining perceptions of female offending : implications for treatment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Kyne, Karen (Massey University, 2006)
Attribution theory is used to provide a conceptual analysis of how personal responsibility and blame are differentially ascribed to fictional male and female offenders. Thirty drug and alcohol counsellors participated; half read a description of a crime committed by a female and the other half read a description of a crime committed by a male. The counsellors rated the offence in terms of the attributional domains of internality, control and stability and then listed potential treatment targets. Offender sex influenced the attribution of blame with counsellors tending to attribute less blame to an offender of the same gender. This effect was particularly pronounced in the case of the female counsellor. Treatment targets were similar for both the male and female offender, with one exception; punishment of some kind was more likely to be considered a necessary outcome when the offender was male.
Keywords: New Zealand; Female offenders